Electrical Energy Harvesting Using Piezoelectric Tiles with Force Amplification Mechanism - Warren Eyu; Hamdan, Rohaiza (Evolution in Electrical and Electronic Engineering, 2022)
The traditional method of generating electricity by burning fossil fuels (coal and oil) such as using a motor to generate the farm would result in increased emissions, therefore, the piezoelectric generator can help decrease the emissions. The sudden power cut off by industrial will affect the well-being of the livestock in the farm. Therefore, the design of a prototype piezoelectric tiles-based chicken/model is introduced. This project is about piezoelectric tiles for poultry purposes. The prototype design piezoelectric tiles help harvest electrical energy from the chicken or model steps. The tile surface must be solid at the electrode and fluid around the surrounding surface. A piezoelectric harvesting system consists of the circuit to convert the AC signal from the piezoelectric material to the DC signal which is used for supplying to charge a 12V DC portable battery. The project uses Proteus software to simulate part of the circuit that is functional and able to supply a small load application. It is a comparison of series and parallel connection with force amplification mechanism. It uses piezoelectric tile and indirectly helps reduce consumer bills. Piezoelectric electrical generation depends on the frequency entry compression on the piezoelectric tiles and it will generate electricity of 1kg weight or more